2022
DOI: 10.25122/jml-2021-0262
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the efficacy of Ginkgo biloba on the cognitive function of patients undergoing treatment with electric shock: a double-blind clinical trial

Abstract: Cognitive impairment is common in patients undergoing electroconvulsive therapy (ECT). Researchers are seeking pharmaceutical compounds with low side effects to decrease these outcomes. This study aimed to investigate the effectiveness of Ginkgo biloba therapy on the cognitive function of patients treated with electroshock. In a double-blinded clinical trial, 80 patients with psychiatric disorders who were candidates for ECT in 2019 were randomly assigned to two groups: the intervention group (receiving Ginkgo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a randomizedcontrolled, double-blind, three-arm trial, patients with hearing loss experienced significant improvements in tinnitus loudness and intensity after 90 days of Ginkgo biloba extract treatment. 105 For psychiatric disorders and cognitive function, a double-blind clinical study revealed that Ginkgo biloba extract led to improvements in patients' Mini-Mental State Examination and Wechsler Memory Scale Recipe III scores without any observed side effects, particularly benefiting older patients. 106 Moreover, Ginkgo biloba extract was also evaluated for its effectiveness, safety, and reliability in treating dizziness caused by cerebral arteriosclerosis in a multi-center, double-blind, randomized controlled trial.…”
Section: Examples Of Some Common Herbs Scientifically Proven To Be Ef...mentioning
confidence: 99%
“…In a randomizedcontrolled, double-blind, three-arm trial, patients with hearing loss experienced significant improvements in tinnitus loudness and intensity after 90 days of Ginkgo biloba extract treatment. 105 For psychiatric disorders and cognitive function, a double-blind clinical study revealed that Ginkgo biloba extract led to improvements in patients' Mini-Mental State Examination and Wechsler Memory Scale Recipe III scores without any observed side effects, particularly benefiting older patients. 106 Moreover, Ginkgo biloba extract was also evaluated for its effectiveness, safety, and reliability in treating dizziness caused by cerebral arteriosclerosis in a multi-center, double-blind, randomized controlled trial.…”
Section: Examples Of Some Common Herbs Scientifically Proven To Be Ef...mentioning
confidence: 99%